Molecular Mechanism of Perfluorooctane Sulfonate-Induced Lung Injury Mediated by the Ras/Rap Signaling Pathway in Mice - Jianhao Peng; Jinfei He; Chenglong Ma; Jiangdong Xue (Toxics)
Perfluorooctane sulfonate (PFOS), a persistent organic pollutant, has raised significant public health concerns because of its widespread environmental presence and potential toxicity. Epidemiological studies have linked PFOS exposure to respiratory diseases, but the underlying molecular mechanisms remain poorly understood. Male C57 BL/6J mice were divided into a control group receiving Milli-Q water, a low-dose PFOS group (0.2 mg/kg/day), and a high-dose PFOS group (1 mg/kg/day) administered via intranasal instillation for 28 days. Lung tissue transcriptome sequencing revealed significantly enriched differentially expressed genes in the Ras and Rap signaling pathways. Key genes including Rap1b, Kras, and BRaf as well as downstream genes, such as MAPK1 and MAP2K1, exhibited dose-dependent upregulation in the high-dose PFOS exposure group. Concurrently, the downstream effector proteins MEK, ERK, ICAM-1, and VEGFa were significantly elevated in bronchoalveolar lavage fluid (BALF). These alterations are mechanistically associated with increased oxidative stress, inflammatory cytokine release, and pulmonary tissue damage. The results indicated that PFOS-induced lung injury is likely predominantly mediated through the activation of the Rap1b- and Kras-dependent BRaf-MEK-ERK axis. These findings highlight the critical role of Ras/Rap signaling pathways in PFOS-associated respiratory toxicity and underscore the need to develop therapeutic interventions targeting these pathways to mitigate associated health risks.